2023
DOI: 10.1186/s40478-023-01547-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal tracking of microglial and monocyte single-cell transcriptomics in lethal flavivirus infection

Abstract: As the resident parenchymal myeloid population in the central nervous system (CNS), microglia are strategically positioned to respond to neurotropic virus invasion and have been implicated in promoting both disease resolution and progression in the acute and post-infectious phase of virus encephalitis. In a mouse model of West Nile virus encephalitis (WNE), infection of the CNS results in recruitment of large numbers of peripheral immune cells into the brain, the majority being nitric oxide (NO)-producing Ly6C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 105 publications
2
15
0
Order By: Relevance
“…Although multiple RNA studies, including our own, have shown that microglia downregulate the expression of the nominal homeostatic microglia-specific markers P2ry12 and Tmem119 during neurodegeneration and neuroinflammation (Jordão et al, 2019;Keren-Shaul et al, 2017;Krasemann et al, 2017;Spiteri, Wishart et al, 2023;Wishart et al, 2022), on a protein level, microglia do not downregulate P2RY12 expression in WNE (Spiteri et al, 2021) or alpha-herpesvirus CNS infection (Fekete et al, 2018). As TMEM119 expression is downregulated by microglia in certain inflammatory diseases, such as WNE, P2RY12 enables the separation of microglia from infiltrating myeloid populations when used in combination with CD45.…”
Section: Staining Single-cell Mouse Brain Suspensions For Microglial ...mentioning
confidence: 91%
See 4 more Smart Citations
“…Although multiple RNA studies, including our own, have shown that microglia downregulate the expression of the nominal homeostatic microglia-specific markers P2ry12 and Tmem119 during neurodegeneration and neuroinflammation (Jordão et al, 2019;Keren-Shaul et al, 2017;Krasemann et al, 2017;Spiteri, Wishart et al, 2023;Wishart et al, 2022), on a protein level, microglia do not downregulate P2RY12 expression in WNE (Spiteri et al, 2021) or alpha-herpesvirus CNS infection (Fekete et al, 2018). As TMEM119 expression is downregulated by microglia in certain inflammatory diseases, such as WNE, P2RY12 enables the separation of microglia from infiltrating myeloid populations when used in combination with CD45.…”
Section: Staining Single-cell Mouse Brain Suspensions For Microglial ...mentioning
confidence: 91%
“…Proceed with manufacturer's instructions for cell capture. Details of sample processing for sequencing can be found in Spiteri, Wishart et al (2023).…”
Section: Single-cell Barcoding With Single-cell Multiplexing Kitmentioning
confidence: 99%
See 3 more Smart Citations